Dietary management in people with an ileostomy: a scoping review protocol. (February 2019) - Mitchell, Alexandra; Perry, Rachel; England, Clare; Searle, Aidan; Atkinson, Charlotte
Abstract : Review question/objective: The objective of this scoping review is to identify and map the evidence for oral dietary management of ileostomies. The primary review question is: what oral dietary strategies for managing ileostomies in humans have been reported? The secondary review questions are: i) what types of evidence have considered oral dietary strategies for managing ileostomies; ii) what aspects of ileostomy management (for example, stoma output or flatulence) are the oral dietary strategies considered to affect; and iii) what sources do people with an ileostomy receive dietary advice from?